If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -5) + 2x = x + 3x + -2x Reorder the terms: 2(-5 + x) + 2x = x + 3x + -2x (-5 * 2 + x * 2) + 2x = x + 3x + -2x (-10 + 2x) + 2x = x + 3x + -2x Combine like terms: 2x + 2x = 4x -10 + 4x = x + 3x + -2x Combine like terms: x + 3x = 4x -10 + 4x = 4x + -2x Combine like terms: 4x + -2x = 2x -10 + 4x = 2x Solving -10 + 4x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + 4x + -2x = 2x + -2x Combine like terms: 4x + -2x = 2x -10 + 2x = 2x + -2x Combine like terms: 2x + -2x = 0 -10 + 2x = 0 Add '10' to each side of the equation. -10 + 10 + 2x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 2x = 0 + 10 2x = 0 + 10 Combine like terms: 0 + 10 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 180+(9x+4)=y | | 20-0.75x+0.55x=10 | | 55+8(25)=x | | 55+8=25 | | -1x^2+4=2x^2-5 | | -20=-10(x+12) | | .40=.5-12 | | 9x-8=9x+6 | | 5x+3(x-4)=8x-12 | | (7)(-6)= | | 12+8x-4=5+2(3x-1) | | 4x+8x+150=164 | | 16(x-2)2-25=0 | | 3(2x+3)=11x+8-5x+1 | | 1x^2+17x+16=0 | | -3-3(8c+7)= | | -8.3x-4.5y+3.4x+3.7y= | | 48=3(2)x | | v-2.9=10.44(46.16568) | | -8=6(x-8) | | 4x-4=-2x+5 | | 4w^2-15w-9=0 | | X^2-1.4x+0.49=0 | | -0.7r-2.1+5.8r-12.8= | | b=2c^2+3c | | x+y+2x=180 | | 3y=127+60 | | 14=7(x+4) | | 250+150(26)=x | | 250+150=26 | | (5)-(9)= | | 3+5(5)=c |